Therapeutic Drug Monitoring of Vancomycin in Hemodialysis Patients in a Hospital in North-East Romania - Aurelia Crețu; Luanda Irina Mititiuc; Iulia-Daniela Lungu; Mihaela Mihaila; Irina Dima; Adrian Covic; Cristina Mihaela Ghiciuc (Antibiotics)
Background/Objectives: Vancomycin is a reserve antibiotic that is frequently prescribed for central venous catheter (CVC)-associated infections in hemodialysis patients. Hemodialysis patients are very fragile patients and the presence of CVCs increases the risk of sepsis. We conducted a prospective study, evaluating the needs of changes in vancomycin dosing for treatment based on the use of the new 2020 vancomycin dosing guidelines, to increase drug safety (preventing subtherapeutic or supratherapeutic doses and offering therapeutic concentrations of the drug) in a particular group of patients with sepsis caused by catheter infections and being on intermittent hemodialysis. Methods: This prospective study included patients with sepsis caused by catheter infections and being on intermittent hemodialysis, treated with vancomycin, admitted in the nephrology department and intensive care unit (ICU). Vancomycin levels were adjusted according to the 2020 vancomycin guidelines. Results: In our study, nine (45%) patients had a vancomycin AUC between 400 and 600 mcg × h/mL, five (25%) patients had a subtherapeutic AUC, and six (30%) patients had a supratherapeutic AUC. It is important to mention that in 10 (50%) of the patients included in the study, the loading and maintenance doses mentioned in the protocol were respected, but 50% of them had a supratherapeutic AUC. We observed that a supratherapeutic AUC occurred when the loading dose was 1500 mg or 2000 mg, and in one case at 1000 mg with a low BMI. Conclusions: a therapeutic level of vancomycin can often be difficult to achieve because of different reasons, mainly in hemodialysis patients.